2015
DOI: 10.1016/j.gde.2015.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic epithelia of the developing vertebrate face

Abstract: A segmental series of endoderm-derived pouch and ectoderm-derived cleft epithelia act as signaling centers in the developing face. Their precise morphogenesis is therefore essential for proper patterning of the vertebrate head. Intercellular adhesion and polarity are highly dynamic within developing facial epithelial cells, with signaling from the adjacent mesenchyme controlling both epithelial character and directional migration. Endodermal and ectodermal epithelia fuse to form the primary mouth and gill slit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 61 publications
1
22
0
Order By: Relevance
“…Even though previous studies have underscored the importance of the endoderm and mesoderm for pharyngeal segmentation, there is limited information on how segmentation is brought about in the endoderm (Graham et al, 2005;Choe and Crump, 2015). In this study, we found that medaka pax1 expression is activated reiteratively in cells where the next pouches will be formed.…”
Section: Impact Of Pax1 On Pharyngeal Segmentation and Derivativesmentioning
confidence: 57%
See 1 more Smart Citation
“…Even though previous studies have underscored the importance of the endoderm and mesoderm for pharyngeal segmentation, there is limited information on how segmentation is brought about in the endoderm (Graham et al, 2005;Choe and Crump, 2015). In this study, we found that medaka pax1 expression is activated reiteratively in cells where the next pouches will be formed.…”
Section: Impact Of Pax1 On Pharyngeal Segmentation and Derivativesmentioning
confidence: 57%
“…Reiterative endoderm expression of pax1 in the segmental development of pouches Compared with segmentation of the somitic mesoderm and hindbrain, there is little information about segmentation of the pharyngeal arches (Graham et al, 2014;Choe and Crump, 2015). Even though previous studies have underscored the importance of the endoderm and mesoderm for pharyngeal segmentation, there is limited information on how segmentation is brought about in the endoderm (Graham et al, 2005;Choe and Crump, 2015).…”
Section: Impact Of Pax1 On Pharyngeal Segmentation and Derivativesmentioning
confidence: 99%
“…Arch patterning occurs between 20 and 30-36 hpf, when pharyngeal arch mesenchyme is divided into major domains by signaling and transcription factors (Alexander et al, 2014; Miller, 2003; Miller et al, 2000; Nichols et al, 2013; Talbot et al, 2010; Zuniga et al, 2010). During this same phase, early endodermal pouch-1 forms (Schilling and Kimmel, 1994) and is a rich source of patterning signals (Choe and Crump, 2015). Then, between 30-36 and 72 hpf, pharyngeal arches undergo dramatic morphogenesis in response to earlier patterning events.…”
Section: Discussionmentioning
confidence: 99%
“…Alcam has been shown to stabilize adherens junctions in epithelial cells (Tomita et al, 2000) or through physical forces to bring adjacent PE cells closer together in zebrafish pouch formation (Choe et al, 2013). To demonstrate that Foxi3 plays a role in invagination and resolving the epithelial layers to form monolayers at E9.0, as well as to determine what downstream effectors may be important for PA segmentation that was reported in zebrafish (Choe and Crump, 2015), we performed immunofluorescence for Alcam on tissue sections from Foxi3 +/and Foxi3 -/embryos at E9.0 when epithelial cells in PA1-2 enter the second transition and begin to resolve to form monolayers and when epithelial cells in PA3 enters the first transition and begins to invaginate and stratify ( Figure 6A-6D). In Foxi3 -/embryos, Alcam expression remained on the basal side of the ectoderm but was strongly reduced on the basal side of the endoderm ( Figure 6D).…”
Section: Alcam and Fibronectin Expression Is Less In Foxi3 Null Embryosmentioning
confidence: 93%
“…The PE and ectoderm cells, together, can be referred to as epithelial cells. The epithelial cells have an important role in PA segmentation and patterning (Campbell et al, 2011;Graham, 2001a, b); (Choe and Crump, 2015;Tsuchiya et al, 2018). Cell adhesion molecules enable cells to assemble together by connecting the internal cell cytoskeletons to determine overall architecture of tissues and intercellular signaling.…”
Section: Process Of Pharyngeal Segmentation In Wildtype Embryosmentioning
confidence: 99%